INDIVIDUAL CREATIVITY AND GROUP ABILITY TO UTILIZE INDIVIDUAL CREATIVE RESOURCES: A MULTILEVEL MODEL. - Taggar, S. (Academy of Management Journal, 2002)
The performance of 94 groups on 13 different open-ended tasks was studied. At the individual-team-member level, domain knowledge and performance-relevant behavioral measures of the three components of Amabile's (1983, 1996) theory of individual creativity related in predicted ways to individual differences. Support was found for new “cross-level” processes, labeled “team creativity-relevant processes.” At the group level, these processes moderated the relationship between aggregated individual creativity and group creativity.